Europeanism, internationalism or something else? Proposal for a cross-lingustic and cross-cultural research project on widespread idioms in Europe and beyond - Piirainen, Elisabeth (HERMES - Journal of Language and Communication in Business, 2005)
Terms like Europeanism or internationalism are used rather carelessly in phraseology research, and they are often applied to idioms accidentally observed to have similar lexical and semantic structures in a few languages. The central question as to what idioms actually constitute the so-called “phraseological uniformity of Europe” has never been studied systematically. The present paper describes my ﬁrst steps of a research project aimed at creating an inventory of factually existing widespread idioms. The total set of idioms is subdivided into smaller groups on the basis of their cultural foundations, thus becoming comparable across a great variety of languages. Questionnaires sent to a large number of idiom research experts are producing ﬁ rst results: numerous idioms are spread across at least several dozens of languages. The problem remains that idioms are currently accessible for only a small portion of the approx. 140 European languages.